PENINGKATAN NILAI KONSTANTA KEKAKUAN PADA SHOCK ABSORBER BEKAS SEPEDA MOTOR DENGAN PROSES ANNEALING - Hadi Kusnanto; Anastas Rizaly; Mochamad Adhita Pangestu F (Rekayasa Sistem Energi dan Manufaktur (ReSEM), 2024)
ABSTRACT Spring is generally used in various machine development, in its use the spring must provide appropriate power, dampen impact, assimilate and store energy to dampen vibration. In this study, an annealing spring combustion process was carried out with large variations in temperature and burning time, then cooled using the normalizing technique. The spring used is the mio soul shockbreaker. The difference in combustion temperature used is 400, 450, 500, with constant testing using a dynamic pressure test. From the research results, it can be seen that there is a change in the value of the stiffness constant due to changes in the annealing heating temperature. When W is 1000N, the annealing temperature is 400 °C : 2500 N/m, 450 °C : 2875 N/m, 500 °C : 2272N/m. The heating temperature that produces the right stiffness constant value is found at a temperature of 450 °C with a constant value at W 1000 N 2875 N/m. Keywords: Spring Constant, Annealing, Shock breaker.